Analisis Perbandingan Waktu Pakai Insert Die Berbahan Baja Perkakas SKD 11, ASSAB 88, dan SKH 51 untuk Produk Mur (NUT) Berbahan S45C - Permana Andi Paristiawan (Fakultas Teknik - Universitas Bung Karno, 2023)
The wear time of die inserts for nut products was studied in this research. The die insert material used is SKD 11, ASSAB 88 and SKH 51 tool steel, while the nut product material to be produced is S45C series carbon steel. These three die insert materials have been tested in the industry. Making nuts includes a dimensional test by measuring the dimensional tolerance of the nut and a service time test by looking at the number of products produced. This test is continued with a microhardness test on the inner side of the die insert. Use time for SKD 11 tool steel is 40,105 products with dimensional tolerance changed to 0.055 mm, ASSAB 88 tool steel is 110,703 products with dimensional tolerance changed to 0.053 mm, SKH 51 tool steel is 100,404 products with dimensional tolerance changed to 0.054 mm, micro hardness test tool steel shows that the deepest part of the die insert side is on average lower than the middle of the die insert. Insert dies made from SKD 11 have the shortest life, Insert dies made from SKH 51 have the longest life, and Insert dies made from ASSAB 88 have the highest life and are slightly higher than SKH 51. The use time for SKD 11 is two to three times, while the use time SKH 51 and ASSAB 88 are estimated to have been used more than three times.